2019
DOI: 10.3390/ijerph16091648
|View full text |Cite
|
Sign up to set email alerts
|

Coupling and Coordination Degrees of the Core Water–Energy–Food Nexus in China

Abstract: Achieving sustainable development in the water–energy–food (WEF) nexus is gaining global attention. The coupling and coordination degrees are a way to measure sustainable development levels of a complex system. This study assessed the coupling and coordination degrees of the core WEF nexus and identified key factors that affect sustainable development. First, an index system for assessing coupling and coordination degrees of the core WEF nexus was built. Second, the development levels of three subsystems as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 35 publications
(34 reference statements)
1
25
0
Order By: Relevance
“…The coupling coordination degree model applied in this paper is mainly derived from the research results of Xu [35], which has been favored in the research on coupling coordination theory in recent years. The calculation steps of the coupling coordination degree model are as follows.…”
Section: A the Coupling Coordination Degree Modelmentioning
confidence: 99%
“…The coupling coordination degree model applied in this paper is mainly derived from the research results of Xu [35], which has been favored in the research on coupling coordination theory in recent years. The calculation steps of the coupling coordination degree model are as follows.…”
Section: A the Coupling Coordination Degree Modelmentioning
confidence: 99%
“…In the future, the WEF nexus faces four major challenges, namely the definition of the system boundary, the uncertainty associated with modeling, restrictions on the internal mechanism, and the evaluation of system performance. Xu et al [20] studied the coupling and coordination degrees of the WEF nexus and found key factors that affected the development levels of WEF. In terms of the research method of the WEF nexus, most of the references mainly adopted qualitative methods, such as an entity model evaluation method.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the interlinkages within the Nexus summarize that 1. water is essential to energy production; 2. energy is necessary to water treatment and distribution; 3. water is required for cultivation and irrigation, crops ensure proper drainage for excess water; and lastly, 4. food security provides continuous energy production, and energy continuously runs industries in food production and transportation [14]. Therefore, the WEF Nexus is viewed as a holistic vehicle to promote sustainable utilization of resources and preserve the ecosystem.…”
Section: B Inexplicit Barriersmentioning
confidence: 99%